COVID-19 pandemic in Saudi Arabia: The decline continues - Mohammed N Al-Ahdal (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
The Kingdom of Saudi Arabia is one of the G20 nations and its global influence is arguably undisputed. The country hosts millions of expatriate residents whose mobility has been affected by the COVID-19 pandemic. Although some countries in Asia, Americas, and Europe do not show signs of recuperation or going through a second wave of the disease, Saudi Arabia has been reporting a decline of the infection. The country is starting to open up its borders for exceptional situations, special cases and trade purposes. It is expected that all travelers will be allowed back and forth normally in Saudi Arabia by early next year, including all those visitors for religious purposes and for tourism.